Validity and reliability of the postgraduate self-determined learning questionnaire (PSLQ) / Melissa Ng Lee Yen Abdullah ... [et al.] - Abdullah, Melissa Ng Lee Yen; Omar, Ahmad Fairuz; Teoh, Ai Ping; Tiew, Chia Chun (Universiti Teknologi MARA, 2022)
Postgraduate students have to play active roles in self-determined learning, as major agent in their own learning and research activities. There is a lack of validated research instruments to measure self-determined learning among postgraduate students. The Postgraduate Self-Determined Learning Questionnaire (PSLQ) was specifically developed to fill in the gaps. This study aims to examine the validity and reliability of the PSLQ through exploratory factor analysis (EFA). The original version of PSLQ has 59 items and it was administered to a sample of 201 postgraduate students from a researchintensive university in Malaysia. The results of EFA revealed that PSLQ measures four distinct factors; learner-centered learning, interactive non-linear learning, double-loop reflection, and capacity development, which accounted for 54.22% of the variance in self-determined learning. The total number of items in PSLQ has been reduced to 42, after 17 items were removed. The instrument demonstrated excellent internal consistency, with a Cronbach’s alpha value of =.959. The findings suggest that PSLQ is a valid and reliable instrument that can be used to measure self-determined learning among postgraduate students. Implications of the research findings are discussed in this paper.